Effects of different soaking intervals on germination and vegetative growth attributes of cape gooseberry (Physalis peruviana L.) under tropical condition - Jahubar, A M J; Sethurathinam, S; Jacob, R; Thiyagarajan, A; Manivannan, U; Veeranan, A G V; Vengadachalpathy, S; Rajadurai, K R; Veeraiah, R; Periyakaruppan, J; Rajendran, S (Plant Science Today, 2025)
The present investigation was carried out to study the effects of different soaking intervals on germination and vegetative growth attributes of cape gooseberry (Physalis peruviana L.) under tropical conditions. The experiment was carried out at the Department of Fruit Science, Horticultural College and Research Institute, Tamil Nadu Agricultural University, Periyakulam, Tamil Nadu, India during October 2024. The five treatments comprised five different soaking intervals of water i.e. T1: one-day soak, T2: two-day soak, T3: three-day soak, T4: four-day soak and T5: control (without soak). Among the five treatments, the highest percentage of germination was recorded in T2 with 93.00 % followed by T1 (77.00 %), T3 (68.00 %) and T5 (control) with 50.00 %, while T4 (40.00 %). The vegetative growth parameters of seedlings were recorded higher in T2 followed by T1, T3, T5 and T4. Two day soaking of seeds registered significant improvement in both seed germination and seedling growth of cape gooseberry.